Uji Efektivitas Ekstrak Daun Pecut Kuda (Stachytarpheta jamaicensis L.) dengan Etanol sebagai Penghambat Pertumbuhan Bakteri Escherichia coli dan Staphylococcus aureus - Ying, Nur Erlina Siah Jia; Setiawan, Nyoman Cahyadi Tri; Rini, Setio; Lestari, Novianti Anggie (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2025)
Infectious diseases remain a global health problem, with antibiotic resistance emerging as a critical challenge due to the irrational use of antibiotics. This research aimed to evaluate the antibacterial activity of Stachytarpheta jamaicensis L. leaves extract with ethanol as an alternative treatment against Escherichia coli and Staphylococcus aureus. A true experimental study with a posttest-only design and control group was conducted using a completely randomized design. The study included 4 treatment groups with extract concentrations of 25%, 50%, 75%, and 100%, alongside 1 positive control and 1 negative control. The inhibition zones for Escherichia coli were 2.5 mm, 3.7 mm, 6.5 mm, and 10.25 mm, respectively, and for Staphylococcus aureus, they were 10.5 mm, 14.75 mm, 18.5 mm, and 21 mm. Positive controls produced inhibition zones of 58 mm for Escherichia coli and 52 mm for Staphylococcus aureus, while negative controls showed no inhibition effect. These results indicate that Stachytarpheta jamaicensis L. leaves extract with ethanol exhibits significant antibacterial activity and may serve as a potential herbal alternative to combat antibiotic-resistant bacteria. Further research is recommended to explore its clinical applications.